NOVICE STUDENTS’ EXPERIENCE OF TAKING TOEIC PREPARATION CLASS: A PHENOMENOLOGICAL CASE STUDY - Rahayu, Nurti; Hamied, Fuad Abdul; Sukyadi, Didi; Yusuf, Fazri Nur (English Review: Journal of English Education, 2022)
This study aims to investigate how novice non-English department students in Indonesia describe their lived experiences of EFL learning in a TOEIC preparation class. The study included eighteen novice students from one vocational higher education in Jakarta who enrolled in a TOEIC preparation class using purposive sampling. Prior to the course, the participants took prediction tests, and their scores fell to the novice learners, and they were required to take a forty-hour preparation class. The participants have taken part in forty-hour TOEIC preparation classes. The primary source of data was semi-structured, in-depth phenomenological interviews. The data were analyzed using thematic analysis. According to the findings, several themes were elaborated. The findings uncovered what students gained and learned from the class, their learning difficulties, their learning strategies, and their plan to improve their English. In this study, the themes were broken down into several sub-themes to better elaborate on the participant's lived experiences and how they made meaning of their experiences. The findings strongly suggest policymakers such as EFL teachers, program and curriculum developers, and other stakeholders pay more attention to the students' voices stating that EFL learning goes to a unique and complex process. Thus, successful English learning cannot be achieved unless their needs and voices are taken into consideration.